GREAT MOSQUE BANDUNG AS A LANDMARK OF BANDUNG CITY - Ecep Herdis Rustandi; Karto Wijaya; Rochmanijar Setiady (Indonesian Journal of Built Environmental and Sustainability, 2019)
ABSTRACT : The city of Bandung is the capital of West Java Province, Bandung City also known as the historic City of Bandung is a witness of historic events from Bandung to the sea of fire until the Asian-African Conference (KAA). The city of Bandung also has historical landmarks of the Dutch colonial era including Gedung Merdeka, Gedung Sate, Savoy Homan Hotel, Pasar Baru, and the Great Mosque of Bandung. Because of the many historic buildings in the city of Bandung, Bandung City is the destination of tourist destinations, both local and foreign tourists, Bandung is also known as Parijs Van Java. The nickname was given because the city of Bandung is located on a plateau surrounded by mountains so that the air or temperature in Bandung is very cool as in Europe. Speaking of historical buildings in this writing, the author will take the title of the Great Mosque as a Landmark of Bandung. The Great Mosque of Bandung Established in the 19th century and is one of the historical buildings in the City of Bandung the Great Mosque Several times experienced transformation of forms or renovations from 1810 - 2001. Bandung Grand Mosque is located in the city square of Bandung or in the center of the city is strategically located making the Bandung Great Mosque a religious tourist attraction in the city of Bandung. Keywords : Mosque, Landmark, Bandung, Colonial, Dutch, Architecture